Dietary intake and plasma phospholipid concentrations of saturated, monounsaturated and trans fatty acids and colorectal cancer risk in the European Prospective Investigation into Cancer and Nutrition cohort. Issue 4 (14th May 2021) - Aglago, Elom K.; Murphy, Neil; Huybrechts, Inge; Nicolas, Geneviève; Casagrande, Corinne; Fedirko, Veronika; Weiderpass, Elisabete; Rothwell, Joseph A.; Dahm, Christina C.; Olsen, Anja; Tjønneland, Anne; Kaaks, Rudolf; et al.
Abstract: Epidemiologic studies examining the association between specific fatty acids and colorectal cancer (CRC) risk are inconclusive. We investigated the association between dietary estimates and plasma levels of individual and total saturated (SFA), monounsaturated (MUFA), industrial‐processed trans (iTFA), and ruminant‐sourced trans (rTFA) fatty acids, and CRC risk in the European Prospective Investigation into Cancer and Nutrition (EPIC). Baseline fatty acid intakes were estimated in 450 112 participants (6162 developed CRC, median follow‐up = 15 years). In a nested case‐control study, plasma phospholipid fatty acids were determined by gas chromatography in 433 colon cancer cases and 433 matched controls. Multivariable‐adjusted hazard ratios (HRs) and odds ratios (ORs) with 95% confidence intervals (CIs) were computed using Cox and conditional logistic regression, respectively. Dietary total SFA (highest vs lowest quintile, HRQ5vsQ1  = 0.80; 95%CI:0.69‐0.92), myristic acid (HRQ5vsQ1  = 0.83, 95%CI:0.74‐0.93) and palmitic acid (HRQ5vsQ1  = 0.81, 95%CI:0.70‐0.93) were inversely associated with CRC risk. Plasma myristic acid was also inversely associated with colon cancer risk (highest vs lowest quartile, ORQ4vsQ1  = 0.51; 95%CI:0.32‐0.83), whereas a borderline positive association was found for plasma stearic acid (ORQ4vsQ1  = 1.63; 95%CI:1.00‐2.64). Dietary total MUFA was inversely associated with colon cancer (per 1‐SD increment, HR1‐SD  = 0.92, 95%CI: 0.85‐0.98), but not rectal cancer (HR1‐SD  = 1.04, 95%CI:0.95‐1.15, P heterogeneity  = 0.027). Dietary iTFA, and particularly elaidic acid, was positively associated with rectal cancer (HR1‐SD  = 1.07, 95%CI:1.02‐1.13). Our results suggest that total and individual saturated fatty acids and fatty acids of industrial origin may be relevant to the aetiology of CRC. Both dietary and plasma myristic acid levels were inversely associated with colon cancer risk, which warrants further investigation. Abstract : What's new? The role of specific fatty acids in cancer development is not fully understood. In this large, prospective European study of colorectal cancer (CRC) risk, the authors found that dietary myristic and palmitic acids from dairy were inversely associated with CRC risk, as were total saturated (SFA) and monounsaturated (MUFA) fatty acids. Dietary industrially‐processed trans fatty acids (iTFA) were positively associated with rectal cancer. These results suggest that total and individual saturated fatty acids may be relevant to the aetiology of CRC.